2010
DOI: 10.3382/ps.2010-00751
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of cyclic heat stress in broilers by dietary supplementation of mannan-oligosaccharide and Lactobacillus-based probiotic: Dynamics of cortisol, thyroid hormones, cholesterol, C-reactive protein, and humoral immunity

Abstract: Heat stress (HS), one of the major problems of tropical and subtropical countries, adversely affects the production performance of poultry. Keeping this in view, the present study was designed to investigate some of the biological markers of HS in broilers as modulated by dietary supplementation of mannan-oligosaccharide (MOS) and a Lactobacillus-based probiotic (LBP), either alone or in combination. Two hundred fifty 1-d-old-chicks were randomly divided into 5 groups. From d 22, the birds were either kept at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
149
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(171 citation statements)
references
References 33 publications
16
149
0
6
Order By: Relevance
“…Additionally, in different studies using a variety of experimental animal models, it was shown that dietary supplementation with MOS lowered plasma cholesterol levels 14, 15, 16. However, the mechanism by which MOS exert their effect is not fully established.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in different studies using a variety of experimental animal models, it was shown that dietary supplementation with MOS lowered plasma cholesterol levels 14, 15, 16. However, the mechanism by which MOS exert their effect is not fully established.…”
Section: Introductionmentioning
confidence: 99%
“…Under high temperature, the bird's body resists to HS by inducing the release of hypothalamic-pituitary hormones, i.e., they regulate their physiological activities, such as metabolism, immunity, and reproduction, etc. via synthesis and release of hormones related to the adrenal axis, thyroid axis, and gonadal axis (Akazome et al, 2002;Elnagar et al, 2010;Sohail et al, 2010;Yin et al, 2011). HS induces the expression of numerous genes, such as heat shock protein 70, growth-and metabolism-related genes (EGFR, SFRP1, and PDK4), immune-related genes (HSF1, Bcl-2, and Bax-α), reproductive hormone receptor-associated genes (LHR, ESR, PRLR, and FSHR), rhythmic genes (Per2), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Broiler chicks fed with prebiotics were increased in weight gain, feed conversation efficiency, nutrient digestibility, while the jejunal content viscosity was decreased (Sundu et al, 2006). On the other hand, dietary supplementation with prebiotics reduced some negative effects of heat stress in broilers (Sohail et al, 2010).…”
Section: Analyzing Mannooligosaccharides By Using Tlc and Hplcmentioning
confidence: 96%